PEMERIKSAAN Human Immunodeficiency Virus PEKERJA WANITA DI BEBERAPA TIMUNG DISTRIK HERAM KOTA JAYAPURA PAPUA - Taroreh, Jannete Elisabeth; Romadhonni, Tika; Rampa, Ester; Balabuana, Gaspar Bao; Indriani, Oktavian; Paembong, Maria Rosari; Sinaga, Herlando; Lobubun, Yusron Mahendra (Universitas Cokroaminoto Palopo, 2025)
Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system. HIV attacks white blood cells, which function as the immune system responsible for fighting infection. Timung is disguised as a traditional massage parlor, but inside there are female sex workers (FSWs) who offer massage services accompanied by sexual services to customers. This study aims to determine the results of HIV testing among female workers in several Timung in the Heram district of Jayapura City. The study was conducted from May 10 to July 30, 2022. The type of research used in this study was descriptive, with a laboratory test approach. The research method used Rapid Immunochromatography and SD Bioline. The population in this study consisted of all female workers in several Timung in the Heram district of Jayapura City, and the sample in this study consisted of 32 venous blood samples. The results obtained from 32 Timung women showed that 30 were HIV-negative and 2 were HIV-positive. Special attention and collective awareness are needed to prevent the spread of HIV from becoming more widespread and threatening the younger generation